(untitled) (Altre Modernità, 2019)
This text compares two anarchist women. The one, Federica Montseny, a Spaniard and the other, Emma Goldman, a Russian émigré to the United States. Both met each other in person thanks to a mutual friend, the Austrian historian Max Nettlau, who encouraged Goldman to visit Spain, a country that had captivated him. Expelled from the U.S. and installed on the French coast, Goldman, exhausted after writing her biography, decided to follow her friend’s advice. Towards the end of 1928, she visited Barcelona and met the Urales family and Federica. It would seem that they did not get along. Although they had much in common, there were also many ideas and experiences that separated them. As I will go on to demonstrate, despite Goldman and Montseny sharing a commitment to anarchism and, being women, also the fight for women emancipation, their family backgrounds, life experiences, personal circumstances, all decisively influenced the different ideological and political perspectives of both. I will argue here that the cause of sexual liberation and, in general, the problems related to sex were much more central to the life and works of Goldman than to those of Montseny. Goldman was far bolder, dared to bring into the public debating arena subjects considered intimate, that belonged to people’s private spheres, and this makes her a far more attractive figure for the newer generations than Montseny.